Can diode laser avoid pilonidal sinus excision by the conventional operation? - Albahadili, Muhammad (Iraqi Journal of Laser, 2021)
Background: Pilonidal sinus is a recurrence pathology that affects the gluteal area, cleft part of it.  It affects many parts but mainly the sacral area and may present with various forms; from the asymptomatic cyst to severe infection in a form of painful abscess or sinus. The treatment of pilonidal sinus ranges from observation with good hygiene to excision of the sinus left wide incision. Recurrence may follow the excisional procedure and may need more operations. Many conservative ways had been used for the management of the sinus; laser (phototherapy) is one kind that may use. this paper aims to test the efficiency of the laser (diode 980nm) in the treatment of the sinus. material: a study of forty-seven patients complaining of the simple pilonidal sinus was managed with laser radiation of diode 980nm, ages of the patients 17- 41-year-old with a mean of 29.15 (SD ± 5.16), the length of the track between 30 mm to 70 mm. and the mean is 46.13 mm. (SD ± 10.32) all primary except 10 patients were recurrent after treatment. result:  the operation was done as a day case, operation time between 6:10 to 14:10 minutes with mean 9:30 minutes. the follow-up of the patients was weekly after seen on 1st postoperative day, with no complication except one infected on 9th day after the operation, which closed on the 21st day after for 10 days with cefixime and metronidazole. the sinus closed in 6 to 30 days with a mean of 12.49. conclusion: laser radiation of diode 980nm can use with good efficacy in pilonidal disease management to avoid the excision of the sinus by conventional procedure which lead to tissues damage, and this decrease the cost, hospital stay, time to return to work, morbidity and complication, we can iterate the procedure without further damage.